นวัตกรรมการบริหารวิชาการโรงเรียนประถมศึกษาสังกัดกรุงเทพมหานครตามแนวคิดสมรรถนะภาวะผู้นำด้านความยั่งยืนของนักเรียน - สุนีย์ บันโนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The objectives of this research aimed to: 1) study the conceptual framework of the students’ sustainability leadership competencies (SSLC) and academic management conceptual framework; 2) study the level of SSLC of Bangkok Metropolitan Administration (BMA) Primary School students; 3) study the current and desirable conditions of academic management based on the concept of SSLC in BMA primary schools; 4) develop an academic management innovation of BMA primary schools based on the concept of SSLC.  It was a multiphase mixed method research design divided into three phases: phase 1 was the empathize step to meet the first research objective; phase 2 were the empathize and the define steps to meet the second and third research objectives.  The population was 431 BMA primary schools; The informants were 1,113 grades 1-6 teachers and school leaders (Principal, Vice-principal, and Heads of the learning subject groups) from 206 sample schools; phase 3 were the ideate step to create prototypes and the test step to conclude to be the academic management innovation to answer the fourth research objective.The research results showed as follows.  (1) The suitable students’ sustainability leadership competencies (SSLC) conceptual framework, comprising 5 essential competencies: 1) sustainability literacy; 2) proactive values; 3) systems thinking; 4) external collaboration; 5) social innovation.  The conceptual framework for academic management consisted of 4 main components: 1) educational policy; 2) curriculum and textbooks; 3) teaching and learning; 4) assessment.  (2) The overall BMA Grades 1-6 SSLC levels were in the "student can do some" level.  When considering Grade 3 students’ SSLC aspects, it was found that "student can do well" in 2 aspects: 1) sustainability literacy and 2) proactive values, while the other 3 aspects were in the "student can do some" level.  For Grade 6 students’ SSLC aspects, it was found that "student can do well" in proactive values, while the other 4 aspects indicating that "student can do some" were: 1) external collaboration, 2) social innovation, 3) sustainability literacy, and 4) systems thinking, respectively.  (3) The overall of the current state of BMA primary school academic management based on the SSLC was at a "moderate" level, while the overall of the desirable condition was at a "high" level, and the rank order of the modified priority needs index to be developed accordingly were: 1) teaching and learning; 2) curriculum and textbooks; 3) assessment; 4) educational policy, and (4) Academic management innovation of BMA primary schools based on the concept of SSLC was the "Academic Management Innovation of BMA Primary Schools focusing on Pedagogy for Enhancing Students’ Sustainability Leadership Competencies (SSLC)", consisting of 3 sub-innovations: 1) Innovation Driving Transformation of Academic Management of BMA Primary Schools focusing on Pedagogy for Enhancing SSLC.  2) Academic Management Innovation of BMA Community Schools focusing on Pedagogy for Enhancing SSLC (grades 1-3), and 3) Academic Management Innovation of BMA Imagineering Schools focusing on Pedagogy for Enhancing SSLC (grades 4-6).